The Influence of Work-Life Balance and Work Environment On Employee Performance With Job Satisfaction As a Mediating Variable at PDAM Tirta Anai Padang Pariaman Regency - Winna Carviona Winna; Muhammad Oceano Fauzan (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to examine the influence of work-life balance, work environment, and job satisfaction on the performance of employees at PDAM Tirta Anai, Padang Pariaman Regency, while also investigating the mediating role of job satisfaction in these relationships. The research employed a quantitative causal-associative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the proposed research model. The study population consisted of all employees of PDAM Tirta Anai, and a saturation sampling technique was applied, resulting in a total sample of 193 respondents. Data were collected through a structured questionnaire and analyzed to assess both direct and indirect relationships among the variables. The findings reveal that work-life balance, work environment, and job satisfaction each have a positive and significant effect on employee performance. Furthermore, both work-life balance and the work environment positively and significantly influence job satisfaction, indicating that employees who experience a better balance between work and personal life, as well as a supportive work environment, tend to report higher levels of job satisfaction. The mediation analysis demonstrates that job satisfaction partially mediates the relationship between work-life balance and employee performance, as well as the relationship between the work environment and employee performance. These findings emphasize the importance of fostering a healthy work environment and promoting work-life balance to improve employee satisfaction and enhance organizational performance.